Influences of the Introduced O-Containing Functional Groups on the Gaseous Pyrolysis Product of Superfine Pulverized Coal - Yang Ma; Yan Gao; Xiumin Jiang (Energies, 2023)
An O-containing structure in coal can affect the pyrolysis process; however, the influence of the introduced O-containing functional groups has rarely been investigated. To study this issue, two kinds of representative coal were selected for superfine pulverization and chemical oxidation. The 13C-NMR and FTIR experiments demonstrated that O-containing functional groups, such as carboxyl, could be added into the carbon skeleton after 5 wt% peracetic acid modification. It was found that 1 wt% and 5 wt% hydrogen peroxide solutions had no such ability, but the 1 wt% solution could expand the pore structure and increase the specific surface area. Thermogravimetric experiments in the air showed that peracetic acid oxidation could increase the weight loss rate below 400 °C and reduce ignition temperatures. Pyrolysis experiments in the tube furnace proved that the amount of CO released increased and the commencing temperature decreased by 50 °C after the modification of peracetic acid. The generation paths of C2H4 and C6H6 changed; new generation peaks appeared near 200 °C. It has been strongly confirmed that superfine pulverization and chemical oxidation modification has obvious synergistic effects on the introduction of O-containing functional groups, especially for anthracite samples.